2016
DOI: 10.1038/srep28863
|View full text |Cite
|
Sign up to set email alerts
|

Optical gain in GaAsBi/GaAs quantum well diode lasers

Abstract: Electrically pumped GaAsBi/GaAs quantum well lasers are a promising new class of near-infrared devices where, by use of the unusual band structure properties of GaAsBi alloys, it is possible to suppress the dominant energy-consuming Auger recombination and inter-valence band absorption loss mechanisms, which greatly impact upon the device performance. Suppression of these loss mechanisms promises to lead to highly efficient, uncooled operation of telecommunications lasers, making GaAsBi system a strong candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…13 These defect-related issues have become a bottleneck in the successful applications of GaAsBi. For instance, to date, GaAsBi-based laser diodes require a threshold current density (2-10 kA cm − 2 ) 6,[14][15][16] that is approximately an order of magnitude higher than that of typical InGaAs-based laser diodes (0.2-0.5 kA cm − 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 These defect-related issues have become a bottleneck in the successful applications of GaAsBi. For instance, to date, GaAsBi-based laser diodes require a threshold current density (2-10 kA cm − 2 ) 6,[14][15][16] that is approximately an order of magnitude higher than that of typical InGaAs-based laser diodes (0.2-0.5 kA cm − 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…All other material parameters are nearly well known and can be found from previous experimental studies reported in the related literature. We use the 12-band • model to calculate the band structure of GaBixAs1-x QWs solar cell, and then compute the optical elements by directly using the calculated QW eigenstates before [15]. The absorption coefficient is shown in Fig.2, [16].…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…In this manner, we are arrived at a 14-band k • p model for like GaBixNyAs1-x-y dilute bismide-nitride alloys. In this model, the band structure of the N-and Bi-containing alloy also can be derived as the lower eigenvalue of the 7- Additionally, the 12-band model (shows inside of the right low black box of the 14-band k • p Hamiltonian) approach is capable of quantitatively describing the optical gain in GaBiAs/(Al)GaAs lasers structures and has already shown excellent agreement for those lasers structures [15]. The parameters we used in this work, such as virtual crystal contributions to CB, VB and SO band edge energies and Bi-related localised states related to the host material VB edge and the VBAC coupling strength can also be found in that reference.…”
Section: Band Structure Modelmentioning
confidence: 99%
“…The theoretical gain spectra were computed as Γg − α i where the material gain g and optical confinement factor Γ were calculated directly for the laser structure [8], and the internal (cavity) losses α i = 15 cm −1 were extracted from optical absorption measurements [9]. In order to compare the measured and calculated spectra, analysis of the measured gain spectrum at each J was undertaken in order to extract a corresponding carrier density n to be used in the theoretical calculations [9]. We note that the calculated gain spectra are in quantitative agreement with experiment, confirming the accuracy of the theoretical model we have developed for dilute …”
Section: Resultsmentioning
confidence: 99%
“…In our model, the material gain spectrum at fixed carrier density is computed by transforming the SE spectrum. The resulting thermodynamic consistency means that each current density (J) in experiment can be associated directly with a carrier density (n) in the theoretical calculations, thereby facilitating direct comparison between theory and experiment [8], [9]. Key to our computation of the optical spectra is the direct use of the QW eigenstates, so that the crucial effects of Bi-induced hybridisation and epitaxial strain are accounted for explicitly.…”
Section: Theoretical Modelmentioning
confidence: 99%